THU0500 Cytokine Production Identifies A Subset of Rheumatoid Arthritis Patients T Lymphocytes That is Associated with Responsiveness to Biologic Anti-TNF-Alpha Agents. (10th June 2014) - Bystrom, J.; Taher, T.; Al-Bogami, M.; Alzabin, S.; Kelly, S.; Mangat, P.; Williams, R.; Jawad, A.; Mageed, R.
Abstract : Background: Biologic anti-TNFα agents have revolutionized the treatment of patients with rheumatoid arthritis (RA). However 30-40% of RA patients do not respond to treatment with these agents. Our studies have suggested that non-responsiveness is due to increased frequency of Th17 lymphocytes. Objectives: To determine if the frequency of T-lymphocyte subsets prior to treatment predicts the response to anti-TNFa agents. Methods: Blood from 70 RA patients prior to and at 4 and 12 weeks post treatment were obtained and level of cytokines in plasma and culture supernatant of stimulated T lymphocytes and monocytes determined. Response to treatment was assessed after 12 weeks by changes in DAS28. Enriched T lymphocytes were stimulated with anti CD3/CD28 and monocytes with LPS. Cytokines levels were determined assessed using a multiplex protocol (MSD technologies). Surface markers and intracellular cytokines expressed by the cells were analysed by FACS. Results: Prior to treatment, responder patients had significantly more TNFα and GM-CSF-producing T lymphocytes than non-responder patients. Intracellular staining revealed that both cytokines were primarily produced by the same T lymphocytes in responder patients. The frequency of TNFα/GM-CSF-producing T lymphocytes was not associated with age nor with gender but patients with high frequency tended to have relatively low DAS28. Interestingly, whilst TNFα/GM-CSF-producing T lymphocytes in responder patient could also produce IL-17, the production of this cytokine was primarily confined to a distinct subset of T lymphocyte in non-responder patients. Finally, plasma levels of GM-CSF were significantly higher in responders compared with non-responders patients prior to treatment. Conclusions: A subset of CD4 + T lymphocytes that produces TNFα and GM-CSF is present at higher frequencies in the blood of RA patients that respond to biologic anti-TNFα agents than in non-responders. This is in contrast to non-responder patients who have higher frequencies of Th17 lymphocytes. Our data may suggest that RA patients could be stratified into responder and non-responder patients to treatment with biologic anti-TNFα based on the T lymphocyte subset that is involved in their disease. Further, measurement of GM-CSF and IL-17 could be useful in identifying responder/non-responder patients prior to treatment. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4637